Educação ambiental crítica: círculos de cultura na formação continuada docente - Oliveira, Laryssa Abílio (2018)
The Critical environmental education in the continuing formation of teachers linked to the conception of Freire's culture circles in schools is important for the promotion of places of dialogue (reflection) and action (practice), so these ideas can be disseminated beyond the walls of these institutions , thus contributing to a sustainable school. The main objective of the thesis was to develop in a public school, a proposal of critical environmental education based on the methodology of Freire 's culture circles, constituting spaces of continuous teacher education that allows for engagement and integration in the whole school community. The study was developed in the public School of Primary and Secondary Education João Roberto Borges de Souza, with the faculty and representatives of the school and community. The study sought to reach all teachers of the school, being developed in the three shifts (morning, afternoon and night), started in February 2015 and extended until July 2017. The research approach is qualitative; the method chosen was the ethnographic one that enabled the understanding of the facts, allowing to document the undocumented and for the analysis of the data was used the theory grounded with the content analysis of Bardin. The research had four main stages: 1st Survey of the structural conditions of the school, identification of the profile of the teachers and enumeration of the difficulties and potentialities of the school for the progress of the project (Questionnaire); 2 ° Delimitation and development of the subjects to be worked in the continuing formation of teachers (Learning and culture circles of Freire); 3 ° Formation of Com-Vida in the school (Focus group - Representatives of the school and community actors) and 4th Comparative analysis of teachers' projects (developed before and during the development of the thesis). In view of the obtained results, it can be concluded that the Sustainable Schools Project, during the year 2015, 2016 and 2017, provided a continuous improvement of the quality of teaching in the target school, contributing to the implementation of a critical and transforming learning modality , however, many were the mishaps that prevented a continuous experience in EE (Environmental Education) compromising the expected progress of the research. It was noticed that some teachers already tried to work the EE in the school, but did it in an isolated, disciplinary way, however, with the experience of the formations based on the culture circles and with the proposal of the sustainable schools, it was already possible a construction and experience of interdisciplinary projects, providing a new experience, based on what recommends the theme. Regarding the projects developed by the teachers, it was observed that they do it in several aspects, mainly after the formations - environmental, social, economic, cultural; thus opening a space for the construction of a curriculum that educates, which perceives its environment and brings it closer to the school. In order to strengthen a critical environmental education based on sustainable schools and the educating city, it is necessary not only to understand the limits and potentialities of the school, but also to build bridges that will strengthen the curriculum, management and buildings. Thus, we are thinking about the need to rethink and devise strategies that allow teachers to rethink their educational practices and realize the importance of working in a critical, contextualized education capable of forming responsible citizens for what happens to them and to the world.